Factors That Influence Compliance to Long-Term Remote Ischemic Conditioning Treatment in Patients With Ischemic Stroke - Zhao, Jie; Fan, Kaiting; Zhao, Wenbo; Yao, Hui; Ma, Jiayue; Chang, Hong (Frontiers in Neurology, 2021)
Objectives: To investigate the treatment compliance of patients with ischemic stroke to remote ischemic conditioning (RIC) and to determine the factors that influence compliance. Methods: We conducted a retrospective study of patients with ischemic stroke who were treated with RIC. Treatment compliance was determined and analyzed in patients who have received one year of RIC training. Factors that influenced patient compliance were also determined using univariate and multivariate regression analyses. Results: Between March 2017 and February 2018, 91 patients were recruited into this study. The mean (±SD) age was 57.98±10.76 years, and 78 (85.7%) patients were male. The baseline Kolcaba comfort scale of patients with good compliance scores were higher than those with poor compliance, The scores of the four dimensions in the scale and the total score are as follows: physiological dimensions, 16.0±4.3 vs 12.6±6.5; psychological dimensions, 30.8±6.8 vs 25.4±12.3; sociological dimensions, 20.6±3.6 vs 17.2±8.3; environmental dimensions, 20.0±5.2 vs 15.6±8.7; and total points, 87.2±18.0 vs 70.1±33.9. The differences between groups were significant (p<0.05). A history of hypertension, number of follow-ups, and the physiological, psychological, and environmental dimensions of the comfort scale were related to patient compliance, out of which the number of follow-ups (OR=2.498, 95% confidence interval (CI) 1.257–4.964) and the physiological discomfort (OR=1.128, 95% CI 1.029–1.236) independently influenced compliance (p<0.05). Conclusion: In patients with ischemic cerebrovascular disease who were treated with RIC, the number of follow-up visits and physiological discomfort associated with RIC treatment independently influenced patient compliance. Further studies are needed to investigate the RIC protocols and their corresponding nursing models.